Protease-activated receptors in vascular smooth muscle cells: a bridge between thrombo-inflammation and vascular remodelling - Anxhela Habibi; Wolfram Ruf; Leon Schurgers (Cell Communication and Signaling)
Abstract Coagulation factors are responsible for blood clot formation yet have also non-canonical functions as signalling molecules. In this context, they can activate protease-activated receptors (PARs) ubiquitously expressed in the vasculature. During vascular repair, vascular smooth muscle cells (VSMCs) will switch from a contractile to a synthetic reparative phenotype. During prolonged vascular stress, VSMCs acquire a pathological phenotype leading to cardiovascular disease. Activated coagulation factors impact on vessel wall permeability and integrity after vascular injury with a key role for PAR activation on endothelial cells. The activation of PARs on VSMCs supports vessel wall repair following injury. Prolonged PAR activation, however, results in pathological vascular remodelling. Therefore, understanding the mechanisms of PAR activation on VSMCs is key to propel our understanding of the molecular and cellular mechanisms to develop novel therapeutic strategies to resolve vascular remodelling. In this review, we discuss recent advances on the role of PAR signalling on VSMCs and specifically their role in vascular remodelling contributing to cardiovascular disease. Additionally, we discuss current therapeutic strategies targeting PAR signalling - indirectly or directly – in relation to cardiovascular disease.